The self on the move : passing through institutional settings - Komatsu, Koji (Perspectives on human development., 2024)
"This volume attempts to delineate the construction of the self in institutional settings of the contemporary world, with the topics ranging from young children to adults and from the micro level to the macro level of human development. The chapters focus on the activities or practices that characterize institutional settings, stressing their dialogical nature that enables understanding human development and the self as what emerge from the dialectic tension of these events-that is, conflicts or contradictions. Discussions included in this volume are different from the principal ways of evaluating institutions in the modern world-i.e., quantitative reports of achievements or merits-but strongly promote further dialogue among researchers or practitioners. This volume offers a new perspective to anyone who are interested in how we psychologically and socially develop in contemporary society, including teachers or practitioners who actually work with children and youths"-- Provided by publisher.